Prevention of Stunting through Cadre Empowerment in the Mangkupalas Health Center Work Area in 2021 - Nursyahid Siregar; Nursari Abdul Syukur; Heni Suryani; Christinawati Br. Haloho; Nino Adib Chifdillah (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Stunting is a chronic malnutrition problem caused by inadequate nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. PKK cadres are one of the pioneers of social change. PKK cadres are often empowered to address various public health problems. The purpose of this community service activity is to carry out empowerment activities for health cadres to prevent stunting in the Mangkupalas Health Center Work Area. The target of the service is the Mangkupalas Health Center Health Cadre. The activity was carried out for 3 months with 2 meetings, namely on September 02 and October 06, 2021. The stages of activity are preparation, implementation, and evaluation. Preparation was carried out by conducting a preliminary survey to see conditions in the field and obtaining a permit for activities at the Mangkupalas Health Center. The implementation is carried out by delivering material on the prevention of stunting since pregnancy with the assistance of health cadres and early detection of stunting with appropriate anthropometric measurements and early detection of stunting under-five development. Evaluation of activities was carried out for each stage with a pretest and posttest. The results of the activity are the empowerment of health cadres in preventing stunting and increasing the ability of health cadres to detect stunting with appropriate anthropometric measurements. The implementation of the activity is done by a team of lecturers and students and assisted by the Mangkupalas Health Center.